Pengungkapan Diri dan Komitmen Pernikahan: Studi Korelasi pada Individu yang Menjalani Commuter Marriage - Laily Qadariyah; Melok Roro Kinanthi (Fakultas Psikologi Universitas Pancasila, 2023)
Commuter marriages face challenges that can affect the commitment of the couple. One of the main concerns in commuter marriages is communication, particularly how individuals can express their needs, thoughts, and feelings to their partners. This research aims to understand the correlation between self-disclosure and marital commitment among individuals in commuter marriages. The research was conducted using a quantitative approach, with a sample of 100 participants selected through convenience sampling. The research variables were measured using The Eight Dimensions of Self-Disclosure for self-disclosure and the Marital Commitment Inventory for marital commitment. The results of the Pearson correlation test showed a significant correlation between self-disclosure and types of marital commitment among individuals in commuter marriages (r = 0.432-0.462; p = 0.000). These findings indicate that efforts to improve the quantity and quality of communication between spouses, especially in expressing personal needs, expectations, feelings, and thoughts, can be made to maintain marital commitment in commuter marriages.